2014
DOI: 10.3340/jkns.2014.55.6.379
|View full text |Cite
|
Sign up to set email alerts
|

Intractable Hiccup as the Presenting Symptom of Cavernous Hemangioma in the Medulla Oblongata: A Case Report and Literature Review

Abstract: A case of intractable hiccup developed by cavernous hemangioma in the medulla oblongata is reported. There have been only five previously reported cases of medullary cavernoma that triggered intractable hiccup. The patient was a 28-year-old man who was presented with intractable hiccup for 15 days. It developed suddenly, then aggravated progressively and did not respond to any types of medication. On magnetic resonance images, a well-demarcated and non-enhancing mass with hemorrhagic changes was noted in the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Brainstem cavernomas can present with a variety of symptoms, rarely including singultus. Spontaneous and familial medullary cavernomas resulting in singultus, while not common, have also been described with one review by Lee et al reporting six patients with a mean age of 34 years (26-40) undergoing surgery [2]. This review found an incidence of hiccups ranging from 3 to 27% with medullary lesions, lesion size ranged from under 1 cm to 2.2 cm and hiccup duration ranged from 15 days to three years, with all patients having a sudden onset.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brainstem cavernomas can present with a variety of symptoms, rarely including singultus. Spontaneous and familial medullary cavernomas resulting in singultus, while not common, have also been described with one review by Lee et al reporting six patients with a mean age of 34 years (26-40) undergoing surgery [2]. This review found an incidence of hiccups ranging from 3 to 27% with medullary lesions, lesion size ranged from under 1 cm to 2.2 cm and hiccup duration ranged from 15 days to three years, with all patients having a sudden onset.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of medullary cavernoma and hiccups is debated, but many theories exist including (1) disruption of the GABA inhibitory control via the raphe magnus nucleus of the hiccup arc [7], (2) irritation of the medullary reticular activating system, near nucleus ambiguus and the obex [8], and lastly (3) involvement of Mollaret’s myoclonic triangle and the olive [2]. Our surgical approach was planned with regards to this anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The medulla oblongata has the vomiting center, and nausea and vomiting result from afferent stimulation. It is known that the reaction center of the hiccup reflex is also in the medulla oblongata [18]. Serotonin and dopamine are neurotransmitters involved in nausea, vomiting, and hiccups as well.…”
Section: Discussionmentioning
confidence: 99%
“…Different central nervous system structures have been hypothesized to underlie the pathological mechanisms of hiccups, such as deep brainstem sites and the medulla oblongata (Tiedt and Wenzel, 2013). Neurological disorders, including medullary infarction and hemorrhage, have reportedly been mechanisms to generate hiccups (Lee et al, 2014). Regarding technical difficulties for accessing brainstem structures, there is growing evidence for the use of novel brain stimulation strategies such as transcranial direct current stimulation (tDCS) for modulating both cortical and subcortical areas.…”
mentioning
confidence: 99%